1988
DOI: 10.1128/mcb.8.8.3008
|View full text |Cite
|
Sign up to set email alerts
|

Small gene family encoding an eggshell (chorion) protein of the human parasite Schistosoma mansoni.

Abstract: We have isolated six independent genomic clones encoding schistosome chorion or eggshell proteins from a Schistosoma mansoni genomic library. A linkage map of five of the clones spanning 35 kilobase pairs (kbp) of the S. mansoni genome was constructed. The region contained two eggshell protein genes closely linked, separated by 7.5 kbp of intergenic DNA. The two genes of the cluster were arranged in the same orientation, that is, they were transcribed from the same strand. The sixth clone probably represents a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 21 publications
(29 reference statements)
1
21
0
Order By: Relevance
“…On the basis of primer extensions and Northern analysis we conclude that a number of schistosome poly(A)+ transcripts carry the identical 36-nt SL sequence at their 5' termini. However, only a subset of S. mansoni poly(A)+ transcripts carry the SL sequence at their 5' termini, since primer extension analyses of transcripts encoding superoxide dismutase (21), egg shell protein (22), calciumbinding protein (23), and an antigen recognized by human sera from infected patients (13) failed to reveal the SL.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of primer extensions and Northern analysis we conclude that a number of schistosome poly(A)+ transcripts carry the identical 36-nt SL sequence at their 5' termini. However, only a subset of S. mansoni poly(A)+ transcripts carry the SL sequence at their 5' termini, since primer extension analyses of transcripts encoding superoxide dismutase (21), egg shell protein (22), calciumbinding protein (23), and an antigen recognized by human sera from infected patients (13) failed to reveal the SL.…”
Section: Resultsmentioning
confidence: 99%
“…When RXR forms heterodimers, such as RXR/RAR and USP/ecdysone receptor, the conformation of its binding partner changes allowing a greater affinity not only for the DNA response element but also for the ligand (43)(44)(45)(46)(47)(48)(49)(50)(51). RT-PCR results demonstrated that SmRXR mRNA is constitutively expressed throughout schistosome development, not only in mature females as are the female-specific genes (2,3,7,9,10). Furthermore, Western blot analysis showed that the 74-kDa SmRXR protein is present in both sexes, mature and immature.…”
Section: Discussionmentioning
confidence: 99%
“…Ligand binding is thought to change the conformation of the steroid receptor into an active state (51). The ability of members of the RXR subfamily to bind specific ligands appears to have evolved after the vertebrate and arthopod lineages diverged, as of yet ligands have not been found for arthropod 10 and 100 ϫ amounts, respectively. Lanes 6 -8, binding reactions contained a 250-bp fragment of a irrelevant DNA competitor in 10, 100, and 250 ϫ amounts, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three clones were identified that shared 100% sequence identity with S. mansoni eggshell proteins. p97D2 encoded the EGG2 ORF (5,16), and both p25G7 and p43F7 encoded the ORF of EGG3 (25). Sex-specific gene products, notably those involved in reproduction, are attractive targets for antihelminth intervention strategies (3) actin I protein (Met-121 to Asp-189) gained a positive C and S score in the SignalP-NN program.…”
Section: Resultsmentioning
confidence: 99%